Molecular characterization and genetic relationship of marigolds (Tagetes spp.) based on simple sequence repeat markers. Issue 3 (December 2014) - Whankaew, Sukhuman; Hasthanasombut, Supaporn; Thaikert, Ratchadaporn; Tappiban, Piengtawan; Smith, Duncan R.; Triwitayakorn, Kanokporn
<x content-type="archive" xml:space="preserve">Abstract</x> In this study, simple sequence repeats (SSRs) specific to marigold were developed using the inter-SSR technique and a SSR-enriched genomic DNA library. In addition, SSRs derived from sunflower (Helianthus annuus) were also tested for transferability to marigold. In total, 38 polymorphic markers with 112 observed alleles were identified in 20 African marigolds (Tagetes erecta L.) consisting of 14 commercial varieties and six Thai landraces, and six French marigolds (Tagetes patula L.). The number of alleles per locus ranged from 2 to 7. The averages of expected and observed heterozygosities were 0.48 and 0.32, respectively. Polymorphic information content values ranged from 0.10 to 0.71, and resolving power (Rp) values ranged from 0.23 to 2.77. The SSRs were successfully applied to the differentiation of the 26 marigold samples into clusters of African commercial varieties, Thai landraces and French marigold. The genetic relationship analysis revealed that the African commercial varieties were more closely related to the Thai landraces than to the French marigold. The results of the study indicate that the SSRs developed are effective for genetic diversity analysis, species classification and individual identification.